The Biopolitics of Feeling : Race, Sex, and Science in the Nineteenth Century - Schuller, Kyla, 1977- (Book collections on Project MUSE., 2018)
In The Biopolitics of Feeling Kyla Schuller unearths the forgotten, multiethnic sciences of impressibility--the capacity to be transformed by one's environment and experiences--to uncover how biopower developed in the United States. Schuller challenges prevalent interpretations of biopower and literary cultures to reveal how biopower emerged within the discourses and practices of sentimentalism. Through analyses of evolutionary theories, gynecological sciences, abolitionist poetry and other literary texts, feminist tracts, child welfare reforms, and black uplift movements, Schuller excavates a vast apparatus that regulated the capacity of sensory and emotional feeling in an attempt to shape the evolution of the national population. Her historical and theoretical work exposes the overlooked role of sex difference in population management and the optimization of life, illuminating how models of binary sex function as one of the key mechanisms of racializing power. Schuller thereby overturns long-accepted frameworks of the nature of race and sex difference, offers key corrective insights to modern debates surrounding the equation of racism with determinism and the liberatory potential of ideas about the plasticity of the body, and reframes contemporary notions of sentiment, affect, sexuality, evolution, and heredity.